2008
DOI: 10.1105/tpc.107.055087
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroids Regulate Grain Filling in Rice  

Abstract: Genes controlling hormone levels have been used to increase grain yields in wheat (Triticum aestivum) and rice (Oryza sativa). We created transgenic rice plants expressing maize (Zea mays), rice, or Arabidopsis thaliana genes encoding sterol C-22 hydroxylases that control brassinosteroid (BR) hormone levels using a promoter that is active in only the stems, leaves, and roots. The transgenic plants produced more tillers and more seed than wild-type plants. The seed were heavier as well, especially the seed at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
264
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 340 publications
(278 citation statements)
references
References 69 publications
10
264
1
3
Order By: Relevance
“…Furthermore, many studies have shown important roles of BR in specific developmental processes. For example, overexpression of BR biosynthetic gene increases grain filling and rice yield (Wu et al, 2008). One of the most sensitive BR responses in rice is lamina joint inclination (Wada et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many studies have shown important roles of BR in specific developmental processes. For example, overexpression of BR biosynthetic gene increases grain filling and rice yield (Wu et al, 2008). One of the most sensitive BR responses in rice is lamina joint inclination (Wada et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the BR signaling-defective mutant d61-7, the weakest mutant of rice BRASSINOSTEROID INSENSITIVE1 (OsBRI1, a protein kinase severing as rice BR receptor), and transgenic rice plants with suppressed expression of OsBZR1 (a transcription factor involved in BR signaling pathway), showed erect leaves [13][14][15]. Conversely, transgenic rice plants overexpressing sterol C-22 hydroxylase, which catalyzes a rate-limiting step in BR biosynthesis, showed a slightly sprawling phenotype with increased leaf angles [16,17]. These results indicate the critical effects of BR, both biosynthesis and signaling, in regulating leaf inclination.…”
Section: Introductionmentioning
confidence: 99%
“…BRs are essential for the elongation of stems and roots and the differentiation of vascular bundles, as well as for senescence, stress response, photomorphogenesis, and tropisms (Mitchell et al, 1970;Clouse, 1996;Li and Chory, 1999;Li et al, 2005). Recently, it has been shown that biomass production and grain yield can be enhanced by controlling the level of endogenous BR in rice (Oryza sativa) plants (Sakamoto et al, 2006;Wu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%